Genome-Wide Association Study of Body Weights in Hu Sheep and Population Verification of Related Single-Nucleotide Polymorphisms - Cao, Yuhao; Song, Xuemei; Shan, Huili; Jiang, Junfang; Xiong, Pei; Wu, Jianliang; Shi, Fangxiong; Jiang, Yongqing (Frontiers in Genetics, 2020)
Body weight (BW) is a critical economic trait for meat production in sheep. The current study aimed to perform a GWAS to detect significant single-nucleotide polymorphisms (SNP) that are associated with BW in Hu sheep. In summary, the comparison and analysis of the G1 and G2 generation of nucleus meat Hu sheep breeding herd revealed 11 SNPs, identified by GWAS, to be associated with BW at a Bonferroni-corrected genome-wide significance threshold of 5%. The subsequent verification of the significant SNP loci in the Hu sheep G3 generation nucleus herd also detected 40 SNPs in significant SNP regions. A total of 8 SNPs significantly associated with the birth weight of Hu sheep were identified (P<0.05). And PCDH7, CNGA3, and ARHGAP24 could be used as candidate genes BW of Hu sheep. The effects of the eight homozygous haplotypes on the transcriptional activity and luciferase hRluc gene expression were explored. T>C mutation at 173 bp upstream of OAR6_110120561.1 was identified as a functional marker associated with the growth traits of Hu sheep that facilitated the discovery of causal variants for BW and contributed to the marker-assisted selection breeding of Hu sheep.